The Relationship Between Self-Regulation and Narcissistic Tendencies Among Students - Maharani, Khofifah Wahyu; Eluemuno, Azukaego Ifeoma (JITSS (Journal of Innovation and Trend in Social Sciences), 2025)
The purpose of this study is to describe the relationship between Self-Regulation and Narcissistic Tendency in students with the research subject consisting of 70 students who are in the social sphere, the majority of whom have a sense of efficacy to anticipate themselves through social media. Posting their activities and personal life through social media in the hope of getting notice or praise from others reduces the sense of empathy, self-esteem, and self-control included in the self-regulation system. Data collection in this study uses the Self-Regulation scale and the Narcissistic Tendencies Scale. The data analysis techniques used were the normality test through SPSS statistic 25 (sig. 0.200 > 0.05 value) and the linearity test (sig. 0.307 > 0.05 value). From the value of the Pearson correlation test, it is known that the significance value of -0.827 > 0.05 between the two variables can be said to be a relationship between the self-regulation variable (X) and narcissistic tendency (Y) which means that the relationship is strongly correlated and has a negative effect.